Different sources of DHA have distinct effects on the ruminal fatty acid profile and microbiota in vitro - Jun Ding; Tengfei Zhan; Jiamei Teng; Yisha Liu; Zhongtang Yu; Lu Ma; Dengpan Bu (Journal of Agriculture and Food Research)
The primary commercial sources for docosahexaenoic acid (DHA, C22:6) are fish oil (FO) and Schizochytrium sp. (SZ). This study aimed to assess how SZ and FO, along with SZ oil (SZO) and pure DHA (pDHA) influence rumen fermentation characteristics, microbiota, and fatty acid profiles in vitro when used at the same concentration. Furthermore, we investigated their effects on microbial protein synthesis. Notably, NH3-N concentration and pH value remained unaffected by the different DHA sources. However, SZ (P < 0.01) and SZO (P < 0.01) enhanced microbial crude protein synthesis compared to the control group (CON). Additionally, pDHA reduced the concentration of total volatile fatty acids (VFA) compared to the other non-pure DHA sources (P < 0.01). The content of branched-chain fatty acids (BCFA) and C22:6 was higher in SZ (P < 0.01) but lower (P < 0.01) in pDHA compared to the other treatments. No difference in C22:6 or BCFA production was observed between SZO and FO. Metataxonomic analysis revealed that all DHA treatments led to a lower relative abundance of Firmicutes (P < 0.01) and a higher relative abundance of Bacteroidota (P < 0.05), Proteobacteria (P < 0.01), and Verrucomicrobia (P < 0.01) compared to CON. Furthermore, the content of C22:6 positively correlated with the relative abundance of the genus Anaerovibrio (P < 0.01, R2 = 0.54) but negatively correlated with the relative abundance of the genus WCHB1- 41 (P < 0.01, R2 = - 0.60). In summary, Schizochytrium sp. powder outperforms DHA-rich oils in enhancing C22:6 and BCFA concentrations in the in vitro rumen fermentation, suggesting its potential for improving dairy production, though further in vivo studies are needed to confirm these benefits.